Integrasi Data SID dan SMS Gateway menggunakan Web Service untuk Layanan Desa Blank Spot Area Data - Andik Wijanarko (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
The village of blank spot data area is a village where most of the area is not covered by internet signals. Villagers experience difficulties in obtaining information, especially information about the requirements of various document processing services in the village office because the village website is difficult to access. As a result, many people must return home because the requirements for processing documents are incomplete so that the acquisition of documents becomes relatively long. The solution is to use an SMS system to request document services. Terms of service will be sent automatically to the SMS sender. The SMS system is integrated with the SID application and has an auto-reply feature. Integration with the SID application using the web service method. The result of the research is a prototype application request based on SMS services that are integrated with the SID application. Time response auto reply this system is six seconds